ANALISIS KECEPATAN PUTARAN MESIN DAN KEDALAMAN PEMAKANAN TERHADAP KEKASARAN PERMUKAAN ALUMUNIUM 6061 - Dimas Bayu Tetuko, (2023)
Turning is a manufacturing process for shaping metal work materials. The turning process will produce a roughness value called the surface roughness value (Ra). Ra is one of the parameters that can be used as a reference in assessing the quality of a metal. Ra is basically influenced by several main parameters including spindle speed and depth of cut. Therefore, the quality level of Ra will affect the quality of the work material. This study aims to determine the quality level of Ra in work materials based on the variations of these two parameters. Turning experiments were carried out using a CNC Turning lathe by varying the spindle speed between 600, 800, 1100 and 1600 rpm and depth of cut of 0.2, 0.4 and 0.6 mm. Then the turning results were tested for the quality of Ra using a Surface roughness tester. From the test results it was found that the lowest Ra of 0.9 µm was found at a spindle speed of 1600 rpm and a depth of cut of 0.2 mm. Furthermore, testing the data is processed using ANOVA to determine the contribution of the two parameters. The ANOVA results show that the F value generated by the rotationalspeed variable is 65.38 which is greater than the F value of the feeding depth, whichis 14.36. This shows that the rotational speed has a greater and dominant influenceon surface roughness